Concealment of Negative Organizational Outcomes: An Agency Theory Perspective - Abrahamson, Eric; Park, Choelsoon (Academy of Management Journal, 1994)
To explore if, when, and how intentionally corporate officers conceal negative organizational outcomes from shareholders, we used computer-assisted content analysis of over 1,000 president's letters contained in annual reports to shareholders. Results suggest that outside directors, large institutional investors, and accountants limit such concealment, but small institutional investors and outside directors who are shareholders prompt it. Low disclosure is associated with subsequent selling of stock by top officers and outside directors. This result supports the claim that concealment by officers and its toleration by outside directors may be intentional.